Developing landscape visual characteristics framework towards promoting place identity of urban aristocrat enclave in Kelantan, Malaysia - Nik Mohammad, Nik Mastura (2019)
The exclusivity of the built cultural landscape in Kota Bharu, Kelantan is historical, tangible and intangible about the importance of preserving the built cultural landscape in aristocrat areas as stated in the Nara Document of Authenticity (1994) and the Burra Charter (1999). Despite the intention stated, the reality is that the new development project in the city have slowly vanished and threatened the new city historical character. The conservation of built cultural landscape aims to balance the activities of the construction and development industry with the maintenance of the health of the built environment while at the same time achieving social, economic, and cultural benefits for present and future generations. This research aim to ascertain the built cultural landscape characteristics of the aristocrat area in Kota Bharu. Besides, this researched is important to preserve and conserve the visual characteristic of built cultural landscape Kota Bharu aristocrat area. Moreover, the research determine on the impact of visual characteristics of built cultural landscape in conserving and preserving Kota Bharu as an aristocrat area. Both quantitative and qualitative methods are used starting from interviewing, focus group and photographic record. Built cultural landscape in Malaysia nominates that only ten percent of overall preservation and conservation development have given over to the place attachment of an aristocrat enclave. A paradigm shift has to exist among the landscape architects, local authorities, NGOs, developers and government agencies. Visual image of the landscape architecture profession in Malaysia, which is known to prioritise physical built cultural landscape appearance into a profession that is able to support our government’s mission to foster social and ethnic integration in Malaysia through sustainable built cultural landscape design. Implementing urban heritage in historic city, a landscape policy associated with old façade building is more preserving by considering the place identity and place attachment to sustain vibrancy of a heritage site.